THE INFLUENCE OF INTEGRITY, COMPETENCE AND WORK EXPERIENCE OF AUDITORS ON AUDIT REPORTS - Nisa, Zahra Ainun; Maghfiroh, Siti; Fitrijati, Krisnhoe Rachmi; Faturokhman, Agus (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
The auditor is expected to produce a reliable audit report that is used as a basis for decision-making. Especially in the quality of audit results, the quality of audit work is assessed from the audit results by the auditor to process the decision-making obtained. One of the quality audit results is conveyed in the form of an audit report. Furthermore, audit reports as formal media used by auditors in communicating to interested parties about the conclusions of the audited financial statements. The purpose of this study is to empirically determine the influence of integrity, competence and work experience of auditors on audit reports. Several factors affect the audit report including integrity, competence and work experience. This research is motivated by the existence of a phenomenon in the form of a discrepancy that exists in audit practice at the inspectorate. The method used in this study is descriptive quantitative. The theory used in this research was attribution theory and the samples in this study were internal auditors in the inspectorates of Banyumas, Purbalingga, Banjarnegara and Cilacap districts. This study used purposive sampling with criteria of the sample they have worked with and experienced for two years. Classical assumption tests are carried out first and data testing is used validity and reliability tests. Furthermore, data were tested using SPSS version 20 using multiple linear regression and hypothesis tests. There are 102 respondents which shows that integrity has a positive effect on audit reports, competence has no effect on audit reports and work experience has no effect on audit reports.